COST ANALYSIS OF CHRONIC KIDNEY DISEASE TREATMENT INPATIENT AS CONSIDERATION DETERMINATION IN HEALTH FINANCING BASED ON INA-DRG IN Dr MOEWARDI HOSPITAL - Fina Ratih Wira Putri Fitri Yani; Ali Ghufron Mukti; Riswaka Sudjaswadi (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Application of INA-DRG (Indonesian Diagnosis Related Group) system for class III of Jamkesmas’s patientsin the hospital has the objective to health services become more effective and efficient both in terms of treatmentand cost planning. The research objective was to analyze the cost of care of patients with Chronic Renal Disease(CRD), find out the relationship between patient factors, concomitant diseases and length of stay with the cost oftreatment and know the difference between the average cost of treatment of CRD according Dr Moewardi Hospital’s tariff and INA –DRG’s package tariff.The study was descriptive and using retrospective data. The subject is limited on class III of Jamkesmas’s patientwith the same period. Variables include demographic characteristics, concomitant diseases, length of stay, costs oftreatment (direct medical costs and direct non-medical costs), and outcome. Analysis data were done with crosstaband linear regression analysis. Result of the research shown that the average cost of treatment chronic renal disease based on Dr Moewardihospital’s tariff on the severity 1st is Rp. 2,870,300 ± Rp 1,634,320, severity 2nd is Rp. 3,659,200 ± Rp. 3,537,470and severity 3rd is Rp. 1,130,690 ± Rp 1,399,252. Average real LOS patient on the severity 1st is 7,00 days, severity2nd is 8.57 days and the severity 3rd is 7.80 days. There was no relationship between patient characteristics andconcomitant diseases with the cost of treatment in hospital, while the length of stay had a relationship withthe cost of treatment. Average treatment costs in chronic kidney failure severity1st, 2nd and 3rd lower than the tariff package INA-DRG, while the average difference in the real LOS, and average LOS INA-DRG severity levels only occurred in three. Keyword : INA-DRG, Chronic Renal Disease, Jamkesmas